MQC: A post-mapping data exploration tool for ribosome profiling. (November 2019) - Verbruggen, Steven; Menschaert, Gerben
Highlights: Ribosome profiling is a new promising sequencing technique for gene expression studies in biomedicine. Tools for checks and data exploration after mapping are currently insufficient for this new NGS technique. mQC offers quality and general feature visualization specific for ribosome profiling. mQC is available in different flavors, also for non-experts. Abstract: Background and objective: Ribosome profiling is a recent next generation sequencing technique enabling the genome-wide study of gene expression in biomedical research at the translation level. Too often, researchers precipitously start trying to test their hypotheses after alignment of their data, without checking the quality and the general features of their mapped data. Despite the fact that these checks are essential to prevent errors and ensure valid conclusions afterwards, easy-to-use tools for visualizing the quality and overall outlook of mapped ribosome profiling data are lacking. Methods: We present mQC, a modular tool implemented as a Bioconda package and also available in the Galaxy tool shed. Herewith both bio-informaticians as well as non-experts can easily perform the indispensable visualization of both the quality and the general features of their mapped P-site corrected ribosome profiling reads. The user manual, the raw code and more information can be found on its GitHub repository (https://github.com/Biobix/mQC ). Results: mQC was tested on multiple datasets to assess its general applicability and was compared to other tools that partly perform similar tasks. Conclusions: Our results demonstrate that mQC can accomplish an unfilled but essential position in the ribosome profiling data analysis procedure by performing a thorough RIBO-Seq-specific exploration of aligned and P-site corrected ribosome profiling data.